Assessment of groundwaterquality and its suitability for agricultural usage in and around rangampeta area,andhra pradesh, South India - Nagaraju, A.; Thejaswi, A.; Sharifi, Z. (Химия и технология воды, 2016)
The aim of this study is to assess the groundwater quality of Rangampeta area for irrigation and domestic purposes. The groundwater samples were analyzed for distribution of chemical elements Ca, Mg, Na, K, Si, HCO₃, CO₃, Cl and SO₄. It also includes pH, electrical conductivity, total hardness, non carbonate hardness and total alkalinity. The parameters like sodium absorption ratio, adjusted sodium absorption ratio, sodium percentage, potential salinity, permeability index and residual sodium carbonate were calculated. The dominant hydrochemical facies of groundwater are Ca-Mg-Cl and Na-Cl Water Types. The Gibbs’s diagram plots suggest that the chemical weathering of rock forming minerals is the major driving force controlling water chemistry in this area. The positive chloro-alkaline indices revealed that the groundwater has suffered ion exchange between Na and K of water with Ca and Mg of soil during its flow.